Branding potential of spas in the Northern Plain and the Mid-Transdanubian Regions - Mosonyi , Attila; Lengyel , Attila; Müller, Anetta (Applied Studies in Agribusiness and Commerce, 2013)
Based on both primary and secondary research in our article we examined the brand elements of the main baths of the NorthernPlain Region (Szolnok Liget Thermal and Experience Bath, Nyiregyháza Aquarius Experience Bath, a Hajdúszoboszló Hungarospa Plc. and the Debrecen Aquaticum Mediterranean Experience bath ) and the Mid-Transdanubian Region (Komárom Medical bath, Agárd Thermal and Medical Bath, Pápa Castle Garden Bath) and worked out their brand systems. We also examined and analysed the possibilities and process of branding. According to their brand elements we established three categories for the baths: Established brands, Developing brands and Brandable baths.